2016
DOI: 10.1007/s00441-016-2501-z
|View full text |Cite
|
Sign up to set email alerts
|

Absence of collagen IX accelerates hypertrophic differentiation in the embryonic mouse spine through a disturbance of the Ihh-PTHrP feedback loop

Abstract: Collagen IX (Col IX) is a component of the cartilage extracellular matrix and contributes to its structural integrity. Polymorphisms in the genes encoding the Col IX ɑ2- and ɑ3-chains are associated with early onset of disc degeneration. Col IX-deficient mice already display changes in the spine at the newborn stage and premature disc degeneration starting at 6 months of age. To determine the role of Col IX in early spine development and to identify molecular mechanisms underlying disc degeneration, the embryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Osteoarthritis (OA) is a type of joint problem, which is often caused by biomechanical factors, and cartilage is the most frequently involved site [1]. Cells located in articular cartilage are differentiated from early to late stage [2]. The superficial zone cells are proliferative, and the deep zone chondrocytes are hypertrophic, from which stage the cells undergo terminal differentiation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a type of joint problem, which is often caused by biomechanical factors, and cartilage is the most frequently involved site [1]. Cells located in articular cartilage are differentiated from early to late stage [2]. The superficial zone cells are proliferative, and the deep zone chondrocytes are hypertrophic, from which stage the cells undergo terminal differentiation [3].…”
Section: Introductionmentioning
confidence: 99%
“…The Ihh is secreted by prehypertrophic chondrocytes to regulate hypertrophy and mineralization of chondrocytes during chondrogenesis [73]. Instead, parathyroid hormone-related protein (PTHrP) can inhibit chondrocyte hypertrophy and maintain chondrocyte proliferation [74,75]. Multiple studies have demonstrated that increased Ihh signaling activates the PTHrP signaling pathway in hypertrophic chondrocytes, causing overexpression of genes associated with cartilage degeneration and the development of OA [76][77][78].…”
Section: Gpr161mentioning
confidence: 99%
“…Visualization of proteoglycans and immunohistochemical staining to detect matrilin-1 (rabbit polyclonal, 1:1000) 27 , matrilin-3 (rabbit polyclonal, 1:1000) 3 and aggrecan (Merck, rabbit polyclonal, 1:100) was performed as described 28 . The 3-amino-9-ethylcarbazole (AEC) substrate-chromogen kit (DAKO) was used for a more sensitive detection.…”
Section: Histology Immunohistochemistry and Immunofluorescencementioning
confidence: 99%